Relational Contracts and the Nature of Market Interactions - Brown, Martin; Falk, Armin; Fehr, Ernst (Econometrica, 2004)
We provide evidence that long-term relationships between trading parties emerge endogenously in the absence of third party enforcement of contracts and are associated with a fundamental change in the nature of market interactions. Without third party enforcement, the vast majority of trades are initiated with private offers and the parties share the gains from trade equally. Low effort or bad quality is penalized by the termination of the relationship, wielding a powerful effect on contract enforcement. Successful long-term relations exhibit generous rent sharing and high effort (quality) from the very beginning of the relationship. In the absence of third-party enforcement, markets resemble a collection of bilateral trading islands rather than a competitive market. If contracts are third party enforceable, rent sharing and long-term relations are absent and the vast majority of trades are initiated with public offers. Most trades take place in one-shot transactions and the contracting parties are indifferent with regard to the identity of their trading partner. Copyright The Econometric Society 2004.